OVERVIEW OF THE CONCEPT OF KHIYAR AL AIB IN E-COMMERCE PRACTICE - Niniek Mumpuni Sri Rejeki (UNIVERSITAS PAKUAN, 2022)
The rapid development of buying and selling online gave birth to various problems related to the shift in traditional buying and selling which developed into buying and selling through the internet world. The ease of transactions obtained through the internet media must be followed by strong protection for consumers, considering that the goods traded cannot be seen and held directly. The choice to determine whether the consumer can continue the sale and purchase contract or cancel it has been regulated in Islamic law, this right to choose is called khiyar. This Khiyar right is a form of protection for consumers. If it is known that the goods traded have defects, then with the validity of khiyar al-aib, consumers can return and replace them with new ones without defects, or cancel the contract with a refund, or can also sincerely accept the defect with a reduced price, all of which are returned to the customer. the parties by mutual agreement. The review of the Khiyar Al-Aib concept in E-commerce in Indonesia by taking the example of the Shopee marketplace aims to analyze that the development of e-commerce is also followed by consumer protection efforts by the application of khiyar al-aib. The research method is normative law by examining a collection of legal materials related to consumer rights, the Consumer Protection Act, provisions in Islamic law. Consumer dissatisfaction with online buying and selling transactions can be followed up with the implementation of the principles and concepts of khiyar al-aib. This review of khiyar al-aib is to understand that the concept of consumer protection in Islam already exists and can be applied to online trading transaction.